Study on the structure-performance relationship between binder types and aluminum-based lithium adsorbent - Ma, Ben; Wang, Xiaoyu; Zhou, Jing; Zhang, Lijuan; Liu, Ruibin; Su, Li; Wang, Wenlong; Wang, Qinglei; Li, Ping; Shangguan, Xuehui; Li, Faqiang (Frontiers in Chemistry, 2025)
Aluminum lithium layered double hydroxides adsorbents (Li/Al-LDH) are used in industry due to their mild adsorption/desorption conditions, good stability and low cost. However, traditional powdered aluminum lithium adsorbents exhibit poor fluidity and a relatively high dissolution rate. The granulation strategy using binders is employed to address the aforementioned challenges. Nevertheless, there is a lack of systematic research on the relationship between the type of binder and the adsorption and desorption efficiency, as well as the kinetics and thermodynamic mechanisms of mass transfer. This work focuses on the structure-activity relationship between adsorbents and three binders (polyvinyl chloride (PVC), polyvinylidene fluoride (PVDF) and calcium alginate (SA)). The experimental results demonstrate that the adsorption/desorption performance of the adsorbent varied significantly with temperature depending on binder type. It is noted that the structures of PVDF-LDH and PVC-LDH changed during temperature changes, resulting in decreased adsorption and desorption performance. While the SA-LDH can maintain good structural stability and adsorption and desorption capabilities. Besides, in 300 ppm LiCl solution, SA-LDH presents a high adsorption and desorption capacity, with the maximum desorption capacity at 40 °C being 5.84 mg/g and the maximum adsorption capacity at 60 °C being 5.67 mg/g. This study elucidates the regulatory mechanisms of temperature on adsorption/desorption behaviors in binder-formulated granulated adsorbents, providing critical insights for optimizing industrial aluminum-based lithium adsorbents in salt lake lithium extraction.